Luz, temperatura e fumaça na germinação de espécies pioneiras da Amazônia central - Aud, Fabiana Ferraz (Instituto Nacional de Pesquisas da Amazônia - INPA, 2008)
In order to highlight the diversity of responses to environmental stimuli in the regeneration by seeds and to clarify whether the responses of germination to such stimuli are related to seed size we compared the effects of light, diurnal variation in temperature and smoke for seven pioneer species from Central Amazon: Bellucia grossularioides, Byrsonima chrysophylla, Cecropia sciadophylla, Croton lanjouwensis, Isertia hypoleuca, Jacaranda copaia and Vismia cayennensis. Each species was subject to three conditions of temperature in light and darkness: 25 °C and alternating temperature of 20-30 ºC and 15-35 ºC for 12 hours. The germination in light and darkness was evaluated with and without solution of smoke water in a concentration of 1:50. For each species, the effects of light, temperature and smoke on the percentage and average time of germination was analyzed by Kruskal-Wallis and Wilcoxon with 5% probability. The influence of the seed mass on germination was tested by simple linear regression versus rates of relative light germination (RGL) and relative germination on alternating temperatures (RGT). We found a relationship between seed size, the type of dormancy and conditions for germination. Although all the seeds of this study were considered photoblastic it was possible to detect a declining demand of light and constant temperature with increasing seed size. The application of smoke water confirmed the negative relationship between seed size and requirement of light and tolerance to alternating temperature. In general, it seems that small seeds need light and constant temperature for germination, the extent to which the amount of the internal resources increases, the seeds become able to germinate in the dark and alternating temperatures.
Keywords: Germinação de sementes; Espécies florestais; Sementes